Multi-project resource allocation under uncertainty: a concept of using resource buffers - Mst Taskia KHATUN; Kazuo HIEKATA; Takuya NAKASHIMA (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
The portfolio manager is responsible for the tactical and operational management of concurrent initiatives that share the same resources. Sharing resources considerably increases complexity by creating resource dependencies between tasks, especially in highly uncertain environments. Therefore, resource allocation in environments with multiple projects is challenging for portfolio managers. According to previous research, classical mathematical approaches effectively address resource and project scheduling issues with low complexity or in a comparatively static environment. However, they have limitations when characterizing interdependencies in multi-project environments, working with uncertainty, and adapting the analysis to dynamic change. This study proposed a simulation method for human resource allocation for multi-project management in a project portfolio system with resource buffers. We have outlined how resource buffers can be allocated in multi-project management and how this impacts portfolio performance. Different quantities of resource buffers have been evaluated in various situations, considering varying degrees of uncertainty and complexity, to determine their impact on performance. In addition, the effect of varying resource buffer sizes on completion time reduction has been studied, which may benefit portfolio/project managers in practice.